The Effect of Trading Halt Events on Market Reactions: The Moderating Effect of MSCI Index Inclusion - Ahmad Jafar Faisal Zuhri; Andi Satriya Kurniawan Pemuda; Harjum Muharam (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Trading halts are widely used by stock exchanges as a market intervention mechanism to facilitate information dissemination and maintain orderly trading during periods of uncertainty. This study examines market reactions to trading halt events by analyzing temporal dynamics and cross-sectional heterogeneity, particularly the moderating effect of Morgan Stanley Capital International (MSCI) index inclusion. Using an event study framework combined with panel regression analysis on a sample of 48 stocks, the findings show that trading halts are associated with statistically significant negative abnormal returns over broader event windows and emerge gradually rather than immediately, indicating delayed price discovery. The results further reveal that the negative impact is less pronounced for MSCI stocks, suggesting that global integration mitigates market responses to trading disruptions. In addition, trading volume exhibits a context-dependent role, reflecting short-term market pressure during the event window but a more conventional positive association in the full sample. The study demonstrates that the effects of trading halts are both time-dependent and heterogeneous across firms, highlighting the importance of firm-level characteristics in shaping market responses. These findings have important implications for regulators and investors seeking to understand price adjustment mechanisms during periods of market interruption.